NLRP3: a new therapeutic target in alcoholic liver disease - Brahadeeswaran, Subhashini; Dasgupta, Tiasha; Manickam, Venkatraman; Saraswathi, Viswanathan; Tamizhselvi, Ramasamy (Frontiers in Immunology, 2023)
The liver is in charge of a wide range of critical physiological processes and it plays an important role in activating the innate immune system which elicits the inflammatory events. Chronic ethanol exposure disrupts hepatic inflammatory mechanism and leads to the release of proinflammatory mediators such as chemokines, cytokines and activation of inflammasomes. The mechanism of liver fibrosis/cirrhosis involve activation of NLRP3 inflammasome, leading to the destruction of hepatocytes and subsequent metabolic dysregulation in humans. In addition, increasing evidence suggests that alcohol intake significantly modifies liver epigenetics, promoting the development of alcoholic liver disease (ALD). Epigenetic changes including histone modification, microRNA-induced genetic modulation, and DNA methylation are crucial in alcohol-evoked cell signalling that affects gene expression in the hepatic system. Though we are at the beginning stage without having the entire print of epigenetic signature, it is time to focus more on NLRP3 inflammasome and epigenetic modifications. Here we review the novel aspect of ALD pathology linking to inflammation and highlighting the role of epigenetic modification associated with NLRP3 inflammasome and how it could be a therapeutic target in ALD.